Chiral-symmetry Breaking and Pion Structure in the Covariant Spectator Theory - Biernat, Elmar P. (2016)
We introduce a covariant approach in Minkowski space for the description of quarks and mesons that exhibits both chiral-symmetry breaking and confinement. In a simple model for the interquark interaction, the quark mass function is obtained and used in the calculation of the pion form factor. We study the effects of the mass function and the different quark pole contributions on the pion form factor.